PENGARUH PEMBERIAN PUPUK HAYATI DAN PUPUK N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annum L.) - Gea, Berkat Harapan Jaya; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to determine the impact of interaction between biofertilizer and N, P, K fertilizer along with the best dosage of biofertilizer and N, P, K fertilizerin increasing growth and yield of red chili. The research was conducted at Experimental Garden of Agriculture Faculty, University of Riau, as long as four months from June to October 2018. The research was done using a Completely Randomized Design (CRD) factorial consist of 2 factors. The first factor was Bioboost biofertilizer concentration that consist of 4 levels (40, 80, 120, and          160 cc.l-1 water per plant). The second factor was dosage of N, P, K Fertilizer that consist of 4 levels (0, 0.25, 0.50, and 0.75% from recommendation dosage of N, P, Kfertilizer). The observed parameters were plant height, days to flowering, days to harvesting, fruit length, fruit diameter, and fruit weight per plant. The observed parameters data were analyzed by variance and followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The result of the research showed that the treatment of bioboost biofertilizer at concentration 120 cc.l-1 and N, P, K fertilizer (Urea at dosage 82,5 kg.ha-1, TSP at dosage 37,5 kg.ha-1 and KCl at dosage              50 kg.ha-1) gave better impact on plant height, days to flowering, days to harvesting, fruit length, fruit diameter and fruit weight per plant compared to the other treatments.Keyword: red chili, bioboost biofertilizer. Urea, TSP, KCl fertilizer